2008
DOI: 10.1088/0268-1242/23/4/045004
|View full text |Cite
|
Sign up to set email alerts
|

Dye-sensitized solar cells using ZnO nanotips and Ga-doped ZnO films

Abstract: Dye sensitized solar cell (DSSC) is a promising and low-cost photovoltaic device. In the DSSC, a monolayer of dye is anchored on the surface of a semiconductor oxide.Photoexcitation takes place inside the dye, and photogenerated charges are then separated at the dye/oxide interface. Nanostructured oxide films are particularly attractive for DSSCs as they provide large surface area for dye anchoring. The crystalline quality of oxide films has significant impact on the charge transport. It is important to reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
68
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 46 publications
3
68
0
Order By: Relevance
“…The DSC performance of these nanotips has been investigated in previous studies. [126,127] The results confirmed that the energy-conversion efficiency of the cells increased with the length of the ZnO nanotips due to the increase in surface area of the photoelectrode film. An overall conversion efficiency of 0.55% was obtained for 3.2-mm-long ZnO nanotips.…”
Section: Zno Nanotubesmentioning
confidence: 52%
See 1 more Smart Citation
“…The DSC performance of these nanotips has been investigated in previous studies. [126,127] The results confirmed that the energy-conversion efficiency of the cells increased with the length of the ZnO nanotips due to the increase in surface area of the photoelectrode film. An overall conversion efficiency of 0.55% was obtained for 3.2-mm-long ZnO nanotips.…”
Section: Zno Nanotubesmentioning
confidence: 52%
“…It has also been demonstrated that the overall conversion efficiency could be increased to 0.77% by combining the ZnO nanotips with a Ga-doped ZnO film as a transparent conducting layer. [127] 3.4. ZnO ''Nanoflowers''…”
Section: Zno Nanotubesmentioning
confidence: 99%
“…What is more, indium is a scarce and toxic material, and thus, the highest share in material cost [13,14] and energy input [15,16] of ITO is inevitable in the fabrication of ITO-based OSCs. Therefore, more and more efforts are dedicated to the ITO-free or indium-free transparent electrodes, such as poly (3,4-ethylenedioxythiophene):-poly(styrenesulfonate) (PEDOT:PSS) [17,18], various transparent conducting oxides (Al-doped ZnO (AZO) or Ga-doped ZnO (GZO)) [19][20][21], Ag nanowires [22,23], carbon nanotubes [24], graphene [25], and so on. However, although the PEDOT:PSS electrode can be prepared by simple solution process, its conductivity needs to be further improved [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, since ZnO is transparent to the whole visible spectrum, it is a good TCO material. Chen et al have recently carried out this concept by growing ZnO nanorods on a ZnO film using a two-step method 18 . In this work we grew ZnO nanorods on a ZnO film using sol-gel technique.…”
Section: Introductionmentioning
confidence: 99%